Penggunaan Gadget Berhubungan dengan Pola Tidur pada Anak Sekolah Dasar di Madrasah Ibtidaiyah Fathan Mubina Ciawi Kota Bogor: The Use of Gadgets and Its Association with Sleep Patterns among Elementary School Children at Madrasah Ibtidaiyah Fathan Mubina, Ciawi, Bogor City - Siti Sari Wulandari; Lannasari Lannasari; Indri Sarwili (Journal of Nursing Education and Practice, 2025)
Introduction: In 2020 gadget users in Indonesia will reach 338.2 million people, of which 79.³% come from the students and children category. Sleep is a process that functions to restore energy and give the body's organs time to rest and to maintain metabolic balance. The use of gadgets can have a negative impact because the effects of gadget radiation can affect health such as disrupting sleep patterns. Objective: to determine the description of gadget use, sleep pattern disorders among MI Fathan Mubina students, as well as the relationship between gadget use and sleep pattern disorders in children at MI Fathan Mubina. Method: This research uses a quantitative research type, namely descriptive correlational with a cross-sectional approach. The sample used in this research was 60 class VI students at MI Fathan Mubina. Data was collected using the SAS (smartphone addiction scale) and SDSC (Sleep disturbance scale of children) questionnaires. Data analysis was carried out in the form of a frequency distribution and used the Spearman Rank correlation test (Spearman Rho). Results: the majority of respondents experienced moderate gadget addiction (80%), and had sleep pattern disorders (91.7%). There is a relationship between gadget use and disturbed sleep patterns with a p-value of 0.035 (<0.05). Conclusion: It is hoped that further research can examine effective nursing interventions that can be applied to treat sleep pattern disorders in elementary school children.